2006
DOI: 10.1007/s00417-006-0456-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of vitrectomy and dye-enhanced ILM peel with grid laser in diffuse diabetic macular edema

Abstract: PPV with ILM peeling was shown to be beneficial by inducing a statistically significant reduction of macular thickness and macular volume. Visual acuity also demonstrated a trend towards improvement in both the ILM peel group and the grid laser group; however, the comparative VA outcome analysis between the two groups was not significantly different. Besides, there was also no correlation between the reductions of foveal thickness and macular volume with the improvement in visual acuity in either of the groups. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 27 publications
(37 reference statements)
4
31
1
1
Order By: Relevance
“…OCT showed a significant improvement in the surgery arm only as well, highlighting the inefficiency of laser rather than a superiority of surgery. Kumar et al [126] prospectively studied 24 eyes with BCVA ≤ 6/60, unresponsive to prior laser, randomizing patients to PPV with ILM peeling or grid laser. There was no difference in mean BCVA gains in both treatment groups, whereas anatomic evaluation showed that surgery improved mean CRT in the surgery group more, but there was no correlation between CRT and BCVA gain.…”
mentioning
confidence: 99%
“…OCT showed a significant improvement in the surgery arm only as well, highlighting the inefficiency of laser rather than a superiority of surgery. Kumar et al [126] prospectively studied 24 eyes with BCVA ≤ 6/60, unresponsive to prior laser, randomizing patients to PPV with ILM peeling or grid laser. There was no difference in mean BCVA gains in both treatment groups, whereas anatomic evaluation showed that surgery improved mean CRT in the surgery group more, but there was no correlation between CRT and BCVA gain.…”
mentioning
confidence: 99%
“…There was also no significant change in either group between baseline and 1-year follow-up. Patel et al 34 and Kumar et al 37,50 have also reported no benefit from similar RCTs, which respectively included 20 and 24 patients with an attached but clinically normal posterior hyaloid. Yanyali et al 41 has however reported an RCT in which 10 patients with bilateral DMO were randomly assigned to vitrectomy on one eye and no treatment on the fellow eye with 12-month follow-up.…”
Section: Introductionmentioning
confidence: 98%
“…15,19,37,41,50,51 Our trial included 40 patients 19 with an attached but otherwise normal posterior hyaloid (ie, no clinical traction or PVD), who were randomised to either more laser or vitrectomy with ILM peeling. We found no clinically or statistically significant difference in acuity or macular thickness reduction between the lasered control and vitrectomy groups at 12 months follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that after removal of the vitreous cortex, with or without internal limiting membrane (ILM) peeling, the release of in the posterior segment, as well as other cytokines released by the ischemic retina (26,27) . In a randomised controlled trial comparing PPV with ILM removal versus focal laser photocoagulation, there was no difference between the two treatments in anatomical or functional outcomes (28) . A randomised pilot study on patients with DMO without macular traction also showed no benefit in terms of visual acuity or macular thickness (29) .…”
Section: Macular Oedemamentioning
confidence: 99%